Effects of acute cardiovascular exercise on motor memory encoding and consolidation: A systematic review with meta-analysis. (September 2020) - Wanner, Philipp; Cheng, Fei-Hsin; Steib, Simon
Highlights: Acute exercise enhances non-sleep and sleep-dependent consolidation. Current evidence does not support benefits on memory encoding. Potential modulating factors were identified by moderator analyses. These include timing and intensity of exercise, as well as motor task nature. More evidence needed to understand interactions between modulating factors. Abstract: Emerging evidence indicates that acute bouts of cardiovascular exercise promote motor memory formation. In this preregistered meta-analysis (CRD42018106288) we synthesize data from 22 studies published until February 2020, including a total of 862 participants. We calculated standardized mean differences (SMDs) with 95 % confidence intervals (CIs) to assess exercise effects on motor memory encoding and consolidation, respectively. The pooled data indicate that exercise mainly benefits the consolidation of memories, with exercise prior to motor practice improving early non-sleep consolidation (SMD, 0.58; 95 % CI, 0.30–0.86; p < 0.001), and post-practice exercise facilitating sleep-dependent consolidation (SMD, 0.62; 95 % CI, 0.34–0.90; p < 0.001). Strongest effects exist for high exercise intensities, and motor task nature appears to be another relevant modulator. We demonstrate that acute cardiovascular exercise particularly promotes the consolidation of acquired motor memories, and exercise timing, and intensity as well as motor task nature seem to critically modulate this relationship. These findings are discussed within currently proposed models of motor memory formation and considering molecular and systemic mechanisms of neural plasticity.